Survey for the detection of Bursaphelenchus insect-vector species in the western part of Turkey - Dayi, Mehmet; Akbulut, Süleyman (Kastamonu University, 2018)
Aim of the study: This study aimed to identify the insect vectors of these Bursaphelenchus species in conifer forests of the western Turkey.Area of study: Sampling was performed in conifer forests of the western part of Turkey.Material and Methods: Two different methods were used, trap trees and pheromone traps with specific lure combinations, to catch insects. Main results: A total number of 11,076 insects in the first year (2012), and 226,205 insects in the second year (2013) surveys were captured. The most represented insect order was Coleoptera and the most common insect species found in all sampling areas was Orthotomicus erosus. After morphological and molecular studies, B. mucronatus was found to be associated with insect bulk samples of Ips sexdentatus, while B. sexdentati was found to be associated with individual and insect bulk samples of O. erosus, Acanthocinus aedilis, and Arhopalus rusticus.
Keywords: Çam Kuruma Hastalığı; Bursaphelenchus türleri; iğne yapraklı ormanlar; vektör böcekler; böcek tuzakları; Pine Wilt Disease; conifer forests; insect traps; Bursaphelenchus species; insect vectors; Pine Wilt Disease; Bursaphelenchus xylophilus; Bursaphelenchus species; conifer forests; insect vectors; insect traps; 15. Life on land